Pengaruh Supervisi Kepala Sekolah terhadap Kompetensi Pedagogik Guru - Anggraini, Mita (Yayasan Sembilan Pemuda Indonesia, 2022)
This study aims to determine the effect of principal supervision on the pedagogic competence of teachers at SD Negeri 104 Palembang. The type of research used is descriptive analysis with a quantitative approach to see the effect of the principal's supervision variable on the teacher's pedagogic competence variable through hypothesis testing. This study uses a questionnaire relevant to the two variables as a means of collecting data which was distributed to 28 respondents from SD Negeri 104 Palembang. Based on the results of the research that has been carried out, there is a positive and significant effect of principal supervision on the pedagogic competence of teachers at SD Negeri 104 Palembang.